Stability of the Gross Motor Function Classification System over time in children with cerebral palsy. (8th August 2022) - Huroy, Menal; Behlim, Tarannum; Andersen, John; Buckley, David; Fehlings, Darcy; Kirton, Adam; Pigeon, Nicole; Mishaal, Ram A.; Wood, Ellen; Shevell, Michael; Oskoui, Maryam
Abstract : Aim: To assess the stability of the Gross Motor Functional Classification System (GMFCS) in children with cerebral palsy (CP) from time of preliminary diagnosis ( 2 years of age) to time of diagnosis ( 5 years of age), and to examine factors associated with reclassification. Method: We conducted a longitudinal study using a sample from the Canadian CP Registry. Stability was analysed by using the percentage of agreement between timepoints and a weighted prevalence and bias adjusted kappa statistic. Univariate and multivariate logistic regressions were performed to identify variables associated with reclassification. Results: The study included 1670 children (857 males, 713 females) with a mean age of 11 years 4 months (SD 4 years, range 3 years 5 months–20 years 1 month) at time of data extraction (3rd September 2019), of which 1435 (85.9%) maintained a stable GMFCS, with a weighted kappa of 0.91 (95% confidence interval 0.89–0.92). Univariate logistic regression showed that initial GMFCS level, CP subtype, and the presence of cognitive impairment were associated with the likelihood of change in the GMFCS level ( p < 0.1). In the multivariate analysis, however, the likelihood was associated with initial GMFCS level only (odds ratio 7.10–8.88, p < 0.00). Interpretation: The GMFCS has good stability in early childhood. For the majority of children, it is predictive of their long‐term motor function. What this paper adds: The Gross Motor Function Classification System (GMFCS) rating in early childhood is stable over time. There is no directionality in the reclassification of the GMFCS. The initial GMFCS level was related to the likelihood of change in follow‐up GMFCS level. What this paper adds: The Gross Motor Function Classification System (GMFCS) rating in early childhood is stable over time. There is no directionality in the reclassification of the GMFCS. The initial GMFCS level was related to the likelihood of change in follow‐up GMFCS level. This original article is commented on by Arnaud on pages 1435–1436 of this issue.